Shifting Patterns of HIV and AIDS in Nepal: A Decadal Review of Evidence and Interventions - Sharma, Akriti; Dhakal, Binita; Basnet, Ijana; Tiwari, Mamata; Gurung, Menu; Adhikari, Narayani (NPRC Journal of Multidisciplinary Research, 2025)
HIV and AIDS in Nepal from 2014 to 2024, focusing on changing transmission patterns, gendered vulnerabilities, and the effectiveness of national responses. Methodologically, this paper is based on a systematic review of secondary sources, including peer-reviewed journal articles, reports from UNAIDS, WHO, and the National Centre for AIDS and STD Control (NCASC), as well as scholarly works by Nepali researchers such as Karki (2014, 2015a, 2015b) and Karki & Gartoulla (2015). Qualitative thematic analysis was applied to synthesize data and identify emerging patterns. Key findings indicate that while overall HIV prevalence in Nepal has declined, new infections persist due to behavioral risks, migration-related vulnerabilities, gender inequality, and socio-cultural stigma. Knowledge about HIV remains high, yet misconceptions and discriminatory attitudes limit preventive practices. Women and marginalized groups remain disproportionately affected due to social dependency and unequal access to services. The conclusion emphasizes that Nepal’s HIV response has improved but remains hindered by structural and cultural barriers. The study recommends strengthening gender-sensitive education, stigma reduction initiatives, and community-based interventions while enhancing data-driven policymaking to sustain progress toward ending AIDS as a public health threat.